2021
DOI: 10.3389/fpsyt.2021.677637
|View full text |Cite
|
Sign up to set email alerts
|

Developing a mHealth Routine Outcome Monitoring and Feedback App (“SMART Track”) to Support Self-Management of Addictive Behaviours

Abstract: Background: Routine outcome monitoring (ROM) has been implemented across a range of addiction treatment services, settings and organisations. Mutual support groups are a notable exception. Innovative solutions are needed. SMART Track is a purpose built smartphone app designed to capture ROM data and provide tailored feedback to adults attending Australian SMART Recovery groups for addictive behaviour(s).Objective: Details regarding the formative stage of app development is essential, but often neglected. Impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
4
11
0
Order By: Relevance
“…According to the youngsters in the panel, feedback is most useful when it involves insight into changes over time, is provided by multiple informants, includes additional information on questionnaires, scales or items and is comprehensive and well-organized. The importance of this value is in line with previous studies [ 12 , 26 , 27 , 28 , 29 ]. Feedback becomes more valuable for youngsters when it provides them with sufficient information to accurately interpret their PROM results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the youngsters in the panel, feedback is most useful when it involves insight into changes over time, is provided by multiple informants, includes additional information on questionnaires, scales or items and is comprehensive and well-organized. The importance of this value is in line with previous studies [ 12 , 26 , 27 , 28 , 29 ]. Feedback becomes more valuable for youngsters when it provides them with sufficient information to accurately interpret their PROM results.…”
Section: Discussionsupporting
confidence: 90%
“…Particularly in light of the new opportunities that digital technologies provide. E-mental health applications have the flexibility to tailor content in a personalized way [ 10 , 11 ] and engage users in real-time [ 12 ]. Both personalisation and real-time engagement have been found to improve responsiveness and patient motivation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preparatory qualitative work [ 63 ] and development process [ 64 ] have been reported separately, and further details are available in the published protocol [ 59 ]. Briefly, three frameworks [ 56 , 65 , 66 ] informed the design, development, and content of SMART Track .…”
Section: Methodsmentioning
confidence: 99%
“…This finding differs from the conclusion of a systematic review of health and well-being smartphone app uptake and engagement conducted by Szinay et al [ 11 ] that reported that study participants who discussed a hypothetical app did not always agree with those who gave their views after actually using an app. Such inconsistency with our findings merits further investigation because the good concordance we identified clearly suggests that soliciting and incorporating end-user views into app design can improve uptake and engagement later [ 30 ].…”
Section: Discussionmentioning
confidence: 92%
“…Taken together, our findings and reflections have potential relevance for other researchers and app developers. For example, we believe that our co-design process was critical in ensuring that SURE Recovery is user friendly, easy to understand, motivating, and trustworthy, and we recommend this collaborative way of working to others [ 8 , 30 ]. Nonetheless, we developed SURE Recovery in response to user demand with limited consideration of our precise target audience and whether we should be including empirically based behavior change techniques [ 2 , 9 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%